2018
DOI: 10.1080/02713683.2018.1501072
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate Ameliorates Oxidative Stress-Induced Retinal Microvascular Dysfunction in Diabetic Rats

Abstract: FA prevents the retinal microvascular dysfunction induced by diabetes, likely by restoring VEGF and P-p65 levels, and possibly by reducing oxidative stress and TXNIP expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Consistent with these previous reports, in the present study, HUCB‐MNC treatment abrogated the increased expression of VEGF in bladders of diabetic rats 4 weeks after the induction of diabetes. Previous studies showed that retinal VEGF gene and protein expression increased significantly in diabetic rats . Furthermore, earlier data reported a permanent increase in renal VEGF gene expression after 3 weeks of diabetes but not in long‐term diabetes .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with these previous reports, in the present study, HUCB‐MNC treatment abrogated the increased expression of VEGF in bladders of diabetic rats 4 weeks after the induction of diabetes. Previous studies showed that retinal VEGF gene and protein expression increased significantly in diabetic rats . Furthermore, earlier data reported a permanent increase in renal VEGF gene expression after 3 weeks of diabetes but not in long‐term diabetes .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that retinal VEGF gene and protein expression increased significantly in diabetic rats. 62,63 Furthermore, earlier data reported a permanent increase in renal VEGF gene expression after 3 weeks of diabetes but not in long-term diabetes. 64 Conversely, Jang et al 65 showed that HUCB-derived mesenchymal stem cells had beneficial effects on renal ischemia-reperfusion injury through humoral effects and the induction of VEGF secretion.…”
Section: Hucb-mncs May Exert Beneficial Effects On Contractions Inducmentioning
confidence: 96%
“…Previous studies have suggested that that fenofibrate exerts robust protective effects against DR in type 2 diabetic patients and type 1 diabetic animal models [ 27 , 28 ]. The potential therapeutic mechanisms of fenofibrate on retinal microvascular dysfunctions induced by diabetes include the restoration of VEGF and the reduction of oxidative stress in diabetic rats [ 29 ]. As CPA4-1 did not alter blood glucose level and HbA1c of db/db mice compared with those of the db/db mice group, CPA4-1 might act as a supplement for the prevention of BRB breakage and retinal acellular capillary formation, without altering blood glucose level or HbA1c of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional therapeutic approaches include: Thiazolidinediones (such as pioglitazone and troglitazone) and synthetic ligands of PPARγ that lead, indirectly, to an increment in production and secretion of adiponectin resulting in the suppression of PASMC proliferation [85]. In the same way, fenofibrate, a PPARγ agonist, ameliorates endothelial functions by reducing levels of inflammation and increasing adiponectin [86,87]. Among antihypertensive drugs, renin–angiotensin system (RAS) blockers have been demonstrated to improve plasma adiponectin levels; specifically, they were more effective than amlodipine, doxazosin, and metoprolol [88,89].…”
Section: Adiponectin Modulation In the Treatment Of Pulmonary Hypementioning
confidence: 99%
“…Finally, promising results have been shown by adipose-derived stem cells (ADSCs) on PAH. Li et al [86] investigated the effects of ADSCs coupled with adiponectin on PAH showing that the ADSCs–adiponectin administration via the jugular vein in mice attenuates the hemodynamic changes and vascular remodeling of PAH (mPAP: 21.44 ± 0.89 mmHg versus 32.62 ± 1.77 mmHg in the PAH group, p < 0.05). Furthermore, the combination of adiponectin and ADSC therapy improved the pulmonary hemodynamics more than ADSC therapy alone (mPAP: 21.44 ± 0.89 mmHg versus 27.11 ± 2.12, p < 0.05).…”
Section: Adiponectin Modulation In the Treatment Of Pulmonary Hypementioning
confidence: 99%